Joint venture: Estimating the size and potential of the UK cannabis market - Christopher Snowdon (Institute of Economic Affairs (IEA), 2018)
This report aims to provide estimates of the size and value of the UK's illicit cannabis market in 2016/17, the size and value of the market if cannabis were legalised and regulated, and the annual tax revenue that a legal cannabis market would yield. Our best estimate suggests that 255 tonnes of cannabis were sold in the UK in 2016/17 at a cost of 2.6 billion to three million consumers. Assuming a pre-tax retail price of 4 per gram and a price elasticity of -0.7, legalisation could cause demand to rise from 255 tonnes to at least 321 tonnes per annum. Total THC consumption would rise by less than this and could even fall if regulation mandated maximum THC levels. A commercialised marijuana market which capped THC levels at 15% would virtually eradicate the black market, but some unlicensed cannabis would remain. If licensed cannabis made up 95% of market, it would produce annual tax revenues of 495 million (with VAT plus a 10%), 557 million (VAT plus a 20%) or 690 million (VAT plus a 30%). The total market size in these three scenarios (including the unlicensed share) would be 339 tonnes, 329 tonnes and 321 tonnes respectively. The highest suggested duty rate of 30% would mean that 36% of the retail price of an average gram of cannabis was tax. This is a lower share of tax than is paid on an average bottle of spirits, litre of petrol or pack of cigarettes in the UK. Although the government could tax cannabis at a higher rate than 30%, this would risk reigniting the black market. Savings to the NHS and other public services are beyond the scope of this report, but previous studies have suggested that they would amount to at least 300 million per annum. When these savings are added to excise tax revenues of 690 million plus new streams of income tax, business tax and VAT created by the legal industry, claims about cannabis legalisation providing a 1 billion windfall to the Treasury seem pessimistic. It is likely that tax revenues alone would exceed this. Meanwhile, lower prices would leave cannabis consumers with more money in their pocket, allowing hundreds of millions of pounds to flow into other areas of the economy.
Keywords: I18; Q13; Q18; Q17; E62; H21; I12; I18; Q13; Q18; Q17; E62; H21; I12; 330